The Political Law of National Economic Development: A Nation of Law Perspective - Ifrani Ifrani (UNIFIKASI : Jurnal Ilmu Hukum, 2021)
Law and economic are the pillars of development. They must be compatible and aligned in the interests of the people. Accordingly, the policy direction of political and economic laws must have value. Thus, the objective of the law can be achieved. In addition, laws are made and built to regulate the business behavior done by investors. These are to protect their economic activities with laws. For these reasons, this research is formulated. This research focused on the following problems: First, how is the concept of law as the basis of economic development? Second, how is the policy direction of political law in National Economic Development? This research employed a normative method and conceptual and historical approach. The findings revealed two ideas: First, five elements such as stability, predictability, fairness, education, and the special development abilities of the lawyer must be developed so that law does not hamper the economy. Second, the policy direction of political law in national economic development is a reflection of the objectives of Indonesian development. Therefore, the development of economic law needs integrated and interdisciplinary skills that require tolerance.